Insights into the genetic history of Green‐legged Partridgelike fowl: mtDNA and genome‐wide SNP analysis. (24th April 2013) - Siwek, M.; Wragg, D.; Sławińska, A.; Malek, M.; Hanotte, O.; Mwacharo, J. M.
Summary The Green‐legged Partridgelike (GP) fowl, an old native Polish breed, is characterised by reseda green‐coloured shanks rather than yellow, white, slate or black commonly observed across most domestic breeds of chicken. Here, we investigate the origin, genetic relationships and structure of the GP fowl using mtDNA D‐loop sequencing and genome‐wide SNP analysis. Genome‐wide association analysis between breeds enables us to verify the genetic control of the reseda green shank phenotype, a defining trait for the breed. Two mtDNA D‐loop haplogroups and three autosomal genetic backgrounds are revealed. Significant associations of SNPs on chromosomes GGA24 and GGAZ indicate that the reseda green leg phenotype is associated with recessive alleles linked to the W and Id loci. Our results provide new insights into the genetic history of European chicken, indicating an admixd origin of East European traditional breeds of chicken on the continent, as supported by the presence of the reseda green phenotype and the knowledge that the GP fowl as a breed was developed before the advent of commercial stocks.